2009
DOI: 10.1007/s12011-009-8362-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Free Zn(2+) Enhancing Inhibitory Effects of EGCG on the Growth of PC-3 Cells: Interactions with Mitochondria

Abstract: Green tea and its major constituent epigallocatechin gallate (EGCG) are known for their chemopreventive effects including those against prostate cancer, which could be mediated by metal ions. Zn(2+) is an essential trace element that is required for human health and plays an important role in the normal function of the prostate gland. In the present study, the effect of EGCG on cell membrane and mitochondria of PC-3 (prostate carcinoma) cells in the presence and absence of Zn(2+) was studied. These studies rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 44 publications
1
15
0
1
Order By: Relevance
“…EGCG associated with heavy metals (eg, Zn 2+ and Cd 2+ ) has reportedly been able to enhance the biological activities of EGCG,41,42 particularly in tumor cell necrosis or apoptosis 41. Shukla et al43 reported that the development of radioactive gold nanoparticles combined with EGCG ( 198 AuNP-EGCG) effectively uploaded nanoparticles onto prostate tumor cells and facilitated EGCG internalization through 67 laminin receptors.…”
Section: Resultsmentioning
confidence: 99%
“…EGCG associated with heavy metals (eg, Zn 2+ and Cd 2+ ) has reportedly been able to enhance the biological activities of EGCG,41,42 particularly in tumor cell necrosis or apoptosis 41. Shukla et al43 reported that the development of radioactive gold nanoparticles combined with EGCG ( 198 AuNP-EGCG) effectively uploaded nanoparticles onto prostate tumor cells and facilitated EGCG internalization through 67 laminin receptors.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental data have shown that in PCa cell lines, a mixture of Zn 2+ and EGCG enhances both the growth inhibitory effect and the free radical scavenging ability with respect to EGCG alone. Moreover, Zn 2+ enhances EGCG effects in terms of reduction of mitochondrial membrane potential and caspase-9 activation [36][37][38]. In PC-3 ML and in IBC-10a primary prostate cell lines, the administration of EGCG (up to 60 μM) determines a reduction of mitochondrial membrane potential and integrity, followed by apoptosis without increase in ROS production [39].…”
Section: Effects Of Gtcs On Intracellular Ros Productionmentioning
confidence: 99%
“…Experimental data have shown that, in PCa cell lines, a mixture of Zn 2+ and EGCG enhances both the growth inhibitory effect and the free radical scavenging ability with respect to EGCG alone. Moreover, Zn 2+ enhances EGCG effects in terms of reduction of mitochondrial membrane potential and caspase-9 activation [36,37,38]. In PC-3 ML and in IBC-10a primary prostate cell lines, the administration of EGCG (up to 60 µM) determines a reduction of mitochondrial membrane potential and integrity, followed by apoptosis without increase in ROS production [39].…”
Section: Effects Of Gtcs On Cellular Redox Homeostasis and Antioximentioning
confidence: 99%